THE ORGANIZATION OF INTERLABORATORY COLLATING TESTS IN THE CENTRAL FACTORY LABORATORY OF THE OJSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - G. N. Voronina (Литьë и металлургия)
The testing laboratory is obliged to plan and realize the actions guaranteeing quality of the carried-out tests. The main directions of this work are:• participation in programs of check of qualification (interlaboratory collating tests (ICT); • application of standard samples; • retests, encoded tests, check by other test method; • statistical control methods.But at the same time it is necessary to use and analyze all sources allowing to estimate quality of the carried-out tests. Such sources could be responses of consumers of production; tests, the procedures of certification of production which are carried out in independent laboratory when carrying out; the ICT organized by both the consumer, and testing laboratory.